Autonomic nervous system and anesthesia [Otonom sinir sistemi ve anestezi] - (:unkn) unknown (Anestezi Dergisi, 2015)
The autonomic nervous system is principally activated by the centers located in spinal cord, brain stem and hypothalamus. It plays an important role in maintaining the homeostasis. Efferent autonomic signals are transmitted to various organs of the body by two major subunits called the sympathetic and parasympathetic nervous system. Tissue activity is increased or inhibited actively as a result of the functions of these two systems. Eventually the regulation of tissue functions is protected in a correct manner. Both volatile and intravenous agents, used in anesthesia practice, produce different effects on sympathetic and parasympathetic systems. In this study we aim to review the autonomic nervous system physiology and the effects of drugs applied in anesthesia on this system.
Keywords: Anesthesia; Autonomic Nervous System; Parasympathetic System; Sympathetic System